The landless? The relevance of the land in the identifications of the Pampean agricultural actors (Huellas, 2019)
For the Pampean agricultural actors the land has been historically considered not only as an economic heritage, but also as symbolic and affective one. In recent decades, the advance of the agribusiness production model questioned the fundamental relationship between subject and land, disarticulating the centrality of the latter as an identity substrate. The discourse disseminated by the defenders of this model in the public sphere re-defines the land as another commodity and addresses the protagonists of production as "the landless".The aim of this paper is to analyze the relevance that the land holds in the identitary constructions of the Pampean agricultural actors and the influence of the agribusiness discourse on those constructions. By considering Stuart Hall’s approach of identifications (2003), we analyse a corpus of 42 interviews carried out between the years 2016 and 2018 in two counties of the province of Buenos Aires which present very different agroecological characteristics (Ayacucho and Baradero), and 329 surveys carried out by our research team in 2013 in the same province.
Keywords: Land; Identifications; Agricultural actors; Agribusiness; Discourse